Impact of Wartime Stress Exposures and Mental Health on Later-Life Functioning and Disability in Vietnam-Era Women Veterans: Findings From the Health of Vietnam-Era Women's Study. Issue 2 (February 2020) - Smith, Brian N.; Spiro, Avron; Frayne, Susan M.; Kimerling, Rachel; Cypel, Yasmin; Reinhard, Matthew J.; Kilbourne, Amy M.; Magruder, Kathryn M.
ABSTRACT: Objective: The effect of stress exposures and mental health sequelae on health-related outcomes is understudied among older women veterans. We examined a) the impact of wartime stress exposures on later-life functioning and disability in Vietnam-era women veterans and b) the extent to which mental health conditions known to be associated with stress—posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and generalized anxiety disorder (GAD)—are associated with additional later-life functioning and disability. Methods: Data were collected in 2011 to 2012 using a mail survey and telephone interview of 4219 women veterans who were active duty during the Vietnam Era. Health functioning was assessed using the Veterans RAND 36-Item Health Survey, and disability was assessed using the World Health Organization Disability Assessment Schedule 2.0. Wartime exposures were assessed using the Women's War-Zone Stressor Scale—Revised; the Composite International Diagnostic Interview, version 3.0 was used to assess PTSD, MDD, and GAD. Results: Several wartime stress exposures—including job-related pressures, dealing with death, and sexual discrimination and harassment—were associated with worse later-life health (β ranges, −0.04 to −0.26 for functioning, 0.05 to 0.30 for disability). Current PTSD was linked with lower health functioning (physical, β = −0.06; mental, β = −0.15) and greater disability (β = 0.14). Current MDD and GAD were also associated with lower mental health functioning (MDD, β = −0.29; GAD, β = −0.10) and greater disability (MDD, β = 0.16; GAD, β = 0.06). Conclusions: Results underscore the importance of detection and treatment of the potential long-term effects of wartime stressors and mental health conditions among women veterans.